Factors influencing adherence to lifestyle prescriptions among patients with nonalcoholic fatty liver disease: A qualitative study using the health action process approach framework - Wang, Lina; Zhou, Huixuan; Liu, Yali; Wang, Xin; Yan, Wenjing; Zhang, Jing; Ren, Hong (Frontiers in Public Health, 2023)
Background and objective: Lifestyle modifications aimed at weight loss have been introduced as a cornerstone of nonalcoholic fatty liver disease (NAFLD) management. However, very few patients can follow the doctor's prescription to change their lifestyle to achieve weight loss in the real world. The purpose of this study is to use the Health Action Process Approach (HAPA) model to explain the determinants to promote adherence to lifestyle prescriptions in patients with NAFLD. Methods: Semi-structured interviews were conducted with NAFLD patients. Reflexive thematic analysis and framework analysis were used to allow naturally identified themes to be determined and then allocated to theoretically driven domains. Results: Thirty adult NAFLD patients were interviewed. Themes were identified and mapped directly on to HAPA constructs. Key barriers to adhering to lifestyle prescriptions related to the coping planning and outcome expectancies constructs of the HAPA model, barriers to physical activity are mainly conditional limits, lack of time, symptoms like fatigue, poor physical fitness and fear of sports injury. Barriers to diet are mainly diet environment, mental stress and craving for food. Key facilitators are simple and specific action planning, coping planning that can flexibly deal with obstacles and difficulties, regular feedback from doctors that can improve self-efficacy, and regular tests and behavior records that help action control. Conclusions: Future lifestyle intervention programs should pay particular attention to planning, self-efficacy and action control-related constructors of the HAPA model to promote the adherence of patients with NAFLD.